Aspek Geometri Pada Perahu Mama Irarat Melan Desa Ritabel Kecamatan Tanimbar Utara Kabupaten Kepulauan Tanimbar: Paulina Prihartini Kanikir, Samuel Urath, Regina Nifmaskossu, Moses Feninlambir* - Paulina Prihartini Kanikir; Samuel Urath; Regina Nifmaskossu; Moses Feninlambir (Samudra Publisher, 2024)
Research on the topic of ethnomathematics is starting to be conducted frequently. Moreover, research that links aspects of mathematics lessons with cultural aspects. This research is motivated by ethnographic and cultural aspects. This research aims to 1) To find out the Geometric aspects contained in the Irarat Melan mama boat of Ritabel Village, North Tanimbar District, Tanimbar Islands Regency, and 2) To find out the symbolic meaning contained in the mama Irarat Melan boat of Ritabel Village, North Tanimbar District, Tanimbar Islands Regency. This research uses qualitative methods with ethnographic design. This research shows that based on the results of research and discussion that has been carried out on the research of Geometric Aspects on Irarat Melan Boat (mama) Ritabel Village, North Tanimbar District, Tanimbar Islands Regency, it can be found that the elements of mathematics contained in the Irarat melan boat culture (mama) there are aspects of geometry such as lines, angles and patterns Some flat planes found on mama boats include; trapezoids, triangles, rectangles, rhombuses, circles. These mathematical aspects can be seen from the mama boat building.